Measuring Public Value: Internet of Things-based Public Safety in Medan City - Afifah, Nur; Nur R., Siti Hazzah; Nurhalizah, Tania (UIR Press, 2026)
Era of digital transformation, the Medan City Police (Polrestabes Medan) have adopted Internet of Things (IoT) based technology encompassing GPS-equipped patrol vehicles and Handy Talkie (HT) communication systems as a strategic innovation to enhance service quality and generate public value. Despite this technological investment, the extent to which IoT implementation has delivered tangible benefits to the community remains critically underexplored. This study aims to assess public value in IoT-based public safety services in Medan City by applying Moore's (1997) Public Value framework as the analytical lens. Employing a descriptive qualitative approach, data were gathered through observation, in-depth interviews with 13 purposively selected informants, and documentation at the Samapta Unit of Polrestabes Medan. Findings reveal that public value has not been fully realized across four key indicators of Moore's framework. First, effectiveness, efficiency, and service coverage remain suboptimal, as crime rates continue to rise, IoT deployment is geographically uneven, and community outreach is virtually absent. Second, while the program broadly aligns with community needs for safety and security, public trust and satisfaction remain low. Third, although police leadership has translated its vision into IoT-based programs, the absence of dedicated technological training for field officers reflects a lack of full operational commitment. Fourth, the community burden has not diminished, with 68% of Medan residents reporting persistent feelings of insecurity in public spaces. This study contributes novel insights by situating public value creation within the specific domain of IoT-enabled public safety — an intersection rarely addressed in the existing Indonesian public administration literature.